Illustrations of Chinese tourism research. (February 2017) - Ryan, Chris; Minghui, Sun; Xiaoyu, Zhang; Li, Fangxuan; Ping, Li; Jun, Gao; Yi, Jin; Lin, Hysin
Abstract: The paper serves as an introduction to this special issue reporting research findings previously published in China's leading tourism journal, Tourism Tribune . It describes the origins of the initial decision to undertake the project, the difficulties experienced, but more importantly comments on the papers. Such comments draw attention to the different traditions of tourism between the West and China, to the role of the Chinese government in the development of tourism, to the role of tourism itself in Chinese policy and the implicit challenges tourism presents as people increasingly see the taking of holidays as part of the 'new normal' of Chinese life under Xi's 'Chinese Dream'. Highlights: Introduces and comments on themes in Chinese tourism research. Notes the issues arising from the comparative newness of social science research in China. Attributes concerns over classifications to a Maoist-Marxist scientific tradition. Identifies tensions over the need of the State to retain control over people's movements and the move to consumerism.